Heart injury in juvenile systemic sclerodermy (clinical case) - Omelchenko, L.I.; Mukvich , O.N.; Belska , O.A.; Dudka , I.V; Klymyshyn, Y.I.; Rudenko , N.M.; Kalashnikova, R.V.; Ismakaieva, D.L.; Vdovina , N.M.; Liudvik , T.A. (Medicni Perspektivi, 2021)
Juvenile systemic sclerosis (JSS) has many clinical manifestations that differ from adults. Early diagnosis is problematic. The course of the disease and the severity of the prognosis depend on the involvement of internal organs in the process, first of all, the heart, lungs, kidneys. Cardiac pathology is a frequent and prognostically unfavorable target of the scleroderma process in adults, but it is rarely diagnosed in children. The aim of the work was to study the features of the clinical manifestations of systemic sclerosis in a child with severe heart disease. A polymorphism of the clinical symptoms of severe heart damage with the development of dilated cardiomyopathy in a one-year-old child with systemic sclerosis is presented. The features of the case are the early debut of systemic sclerosis in a child with a burdened hereditary history of autoimmune pathology (psoriasis in the father and grandmother), rapid progression of the autoimmune process, severe heart damage by the type of non-compact (dilated) cardiomyopathy, positive clinical dynamics when using pathogenetic therapy. Early detection of cardiovascular lesions using modern diagnostic methods, timely implementation of adequate therapy in a multidisciplinary team and regular cardiovascular screening can improve the prognosis, quality of life and reduce mortality.